2018
DOI: 10.1002/adma.201706981
|View full text |Cite|
|
Sign up to set email alerts
|

Surface Nanopore Engineering of 2D MXenes for Targeted and Synergistic Multitherapies of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common and deadly gastrointestinal malignancies. Given its insensitivity to traditional systematic chemotherapy, new therapeutic strategies for efficient HCCs treatment are urgently needed. Here, the development of a novel 2D MXene-based composite nanoplatform for highly efficient and synergistic chemotherapy and photothermal hyperthermia against HCC is reported. A surface-nanopore engineering strategy is developed for the MXenes' surface functionalization, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(117 citation statements)
references
References 54 publications
1
116
0
Order By: Relevance
“…Copyright 2016, American Chemical Society. (F) Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Inorganic Contrast Agentsmentioning
confidence: 99%
“…Copyright 2016, American Chemical Society. (F) Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Inorganic Contrast Agentsmentioning
confidence: 99%
“…The tumor‐targeting ability of Ti 3 C 2 @mMSNs was improved after modification by RGD. This nanocomposite showed high DOX loading capacity and pH‐ and NIR light‐responsive controllable release, which could effectively eradicate the tumor …”
Section: D Nanomaterials For Ptt‐based Synergistic Therapymentioning
confidence: 99%
“…(F) Schematic illustration of pH/photothermal-triggered drug release from DOX-loaded Ti 3 C 2 @mMSNs-RGD [105]. (G) Cumulative DOX release from DOX-loaded Ti 3 C 2 @ mMSNs-RGD in phosphate-buffered saline (pH 7.4) as triggered by 808 nm NIR lasers at elevated power density [106].…”
Section: Chemotherapy and Pttmentioning
confidence: 99%
“…Because of its insensitivity to traditional systemic chemotherapy, new effective treatment strategies are urgently needed. Li et al reported a new 2D-MXene composite nanoplatform for high-efficiency synergistic chemotherapy and photothermal hyperthermia for liver cancer ( Figure 7G) [106]. The surface nanopore engineering method is used to realize the multifunctionality of Ti 3 C 2 -based MXene, and a thin layer of mesoporous silica is uniformly coated on the surface of 2D-MXenes.…”
Section: Chemotherapy and Pttmentioning
confidence: 99%